Enzymatic Synthesis of the C-glycosidic Moiety of Nogalamycin R - Siitonen Vilja; Nji Wandi Benjamin; Törmänen Akke-Pekka; Metsä-Ketelä Mikko (ACS Chemical Biology, 2022)
Carbohydrate moieties are essential for the biological activity of anthracycline anticancer agents such as nogalamycin, which contains l-nogalose and l-nogalamine units. The former of these is attached through a canonical O-glycosidic linkage, but the latter is connected via an unusual dual linkage composed of C–C and O-glycosidic bonds. In this work, we have utilized enzyme immobilization techniques and synthesized l-rhodosamine-thymidine diphosphate (TDP) from α-d-glucose-1-TDP using seven enzymes. In a second step, we assembled the dual linkage system by attaching the aminosugar to an anthracycline aglycone acceptor using the glycosyl transferase SnogD and the α-ketoglutarate dependent oxygenase SnoK. Furthermore, our work indicates that the auxiliary P450-type protein SnogN facilitating glycosylation is surprisingly associated with attachment of the neutral sugar l-nogalose rather than the aminosugar l-nogalamine in nogalamycin biosynthesis.